Analysis of deformation failure and stability of slope coal under different mining conditions - WANG Wencai; LI Junpeng; WANG Chuangye; CHEN Shijiang; LI Shizhang (Meikuang Anquan, 2023)
Due to the typical instability characteristics of the slope, slope coal mining will further aggravate the deformation and instability of the slope. Therefore, we use FLAC3D slope structure model to analyze and predict the deformation, failure and stability of the slope coal under different mining conditions. The result shows that the expansion form and range of the plastic zone of the rock mass inside the slope are different different mining conditions, and the disturbance and damage to the slope flat plate are also different; compared with the downhill stoping, the uphill stoping is worse than the downhill stoping in terms of length and slope stability; the downhill stoping can ensure the stability of the slope to a certain extent; although there is a local slip phenomenon, the overall stability is better, and the instability phenomenon exists in the reverse slope mining slope; the upper coal seam mining slope has local instability, and the overall stability is good. The lower coal seam plastic zone is far away from the slope flat plate, and its stability is better than that of the upper coal seam. It can be concluded that the slope stability is related to the mining depth. The greater the mining depth, the better the slope stability.